Antibiotic Resistance: A Universal Issue of Concern - Khan, Hashim; Malik, Abdul; Gaur, Praveen Kumar; Rastogi, Sameer; Lata, Kanak (Journal of Pharmacy Practice and Community Medicine)
The antibiotic resistance forthwith is the worldwide severe health problem. Clinical and economically, outcomes are harmed by the antibiotic resistance, along with consequences ranging from a patient’s failure to respond treatment and the expensive and alternative drugs costs higher morbidity and mortality rates, preponderant hospital stays and the need for changes in standard therapy. The usage of antibiotic in the population as a whole a few leading sources of antibiotic resistance. Patients who do not have a prescription are frequently given ‘prescription-only’ medications like antibiotics by pharmacists in undeveloped nations like India. There is a lack of information on how community pharmacists use antibiotics which is critical for developing a viable and long-term intervention programmed to encourage judicious antibiotic use. Antibiotics are one of the most effective weapons to fight against life-threatening illnesses. Their discoveries have a significant impact on human as well as animal health. Consequently, because of the advent and spread of antimicrobial resistance, people all around the world including Americans are sinking due to intractable diseases. In this review, we will look at the trapping of antibiotic resistance on the general public health, community, society and health care system. Resistance to antibiotics is a danger sign that is putting strain on healthcare systems and resulting in severe health loss; we must continue to monitor and support activities aimed at preventing and controlling the infection.
Keywords: Clinical Pharmacist; Infection Control Team; Prescribers